Comunicação, recepção e consumo entre o Guarani: o ínido na mídia e a mídia na vida do índio - Vendrame, Sonia Ines (2009)
This thesis discuss the media scene in the village located Tekoha Añetete in Diamante do Oeste, Paraná, and their interactions with the traditional culture, Checking, thus the reception of cultural products through daily practices. The objective is to check how is the reception of media products through the media-event of the meeting tradition in social and cultural practices of families. To understand the communication processes with emphasis on the reception, we adopted multimetodos, namely: ethnographic observation, map of cultural consumption, focus group interviews and in depth. This set of data is analyzed based on the theoretical axis communication, consumption and reception. The magic performed on television by the residents was evident. It is the screen that spring guidelines for the livelihood of the village. The Opy (houses of prayer) is no longer in the place of the renewal of the spirit; lost space for recreation rooms and the brightness of displays. The chamoy (olds) of the village no longer exercise leadership, authority is young and with eyes off the reservation. The clothes follow the latest fashion dictated by TV, the soap; foods are those that advertising conveys. The resistance of a few mixed up the drive time. You can see in the cultural practices of families, the presence of the media, especially TV.